Online didactical design for subtraction fractions: A didactical design research through lesson study activities - Kuswara, R. Didi; Almazroei, Essa Eqal; Isnawan, Muhamad Galang (International Journal of Didactic Mathematics in Distance Education, 2024)
The COVID-19 pandemic disrupted educational practices worldwide, posing significant challenges for students, particularly in mastering foundational mathematical concepts such as fraction subtraction. In response to the urgent need for effective remote learning strategies, this study aimed to develop and implement an online didactic design to reduce student learning obstacles. Employing a Didactical Design Research (DDR) approach, the design process was supported by lesson study activities at each developmental phase to ensure instructional quality. Participants included 56 students from grades VII and VIII (ages 13 to 18). The researcher served as the primary instrument, supported by additional tools including a fraction test, interview guide, documentation study, and the online didactic design itself. Thematic analysis was used to identify learning barriers, while qualitative analysis assessed the effectiveness of the design implementation. Findings revealed that during the pandemic, students experienced both ontogenic and epistemological learning obstacles in subtracting fractions. However, after the online didactic design was introduced and implemented, these learning barriers were no longer evident. Remaining difficulties were attributed to internal, non-instructional factors, such as limited personal study time, rather than issues related to instructional delivery.  This study contributes to the field of mathematics education by providing an empirically grounded model for designing online instruction that addresses specific learning barriers. The findings underscore the importance of aligning didactic design with student learning needs, especially in crisis contexts, and highlight the potential of structured online approaches to support equitable mathematics learning.